A construção do currículo nos novos espaços de design secundário. O Holocausto como proposta de pesquisa no Seminário de Ciências Sociais - RAYNOLDI, GUSTAVO DANIEL (Universidad Nacional del Litoral, 2020)
This article deals with some aspects of thenew articulated area for secondary level: the Seminarof Social Sciences. Its innovative potential and sometensions detected between curricular design and itsimplementation are addressed through an experiencewith students attending the second year of Juan MarcosSecondary School in the city of Santa Fe, Argentina,who worked on case studies about the Shoah, the process of persecution and extermination suffered by theEuropean Jewish people under the national socialistregime of the German Third Reich before and duringthe Second World War. The curricular proposal wasdefined according to the curriculum designed by theProvincial Ministry of Education in relation to the Seminar, the decisions of incorporating subjects related tothe Holocaust in our educational jurisdiction, and theteaching training course on the Shoah offered by theprovincial government. The experience brought abouthigh motivation in various ways, which we tried to relateto the Seminar area that was still being constructed.